2020
DOI: 10.30598/mjocevol10iss2pp81-88
|View full text |Cite
|
Sign up to set email alerts
|

Preparasi Dan Karakterisasi Arang Dari Ampas Sagu Sebagai Adsorben Dalam Menurunkan Kadar Cod Dan Bod Limbah Cair Pabrik Tahu

Abstract: The preparation and characterization of charcoal from sago pulp as an adsorbent in reducing content of COD and BOD of tofu factory waste has been carried out. Sago pulp has been turned into charcoal through carbonization at 400oC for 2 hours. The results of charcoal characterization using XRD show that the carbon produced from sago pulp carbonization has a low crystallinity which is indicated by a wide peak at around 2θ 23oC, which is the characteristic carbon peak. The results of characterization using Surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Goa, et al (2014) reported the use of palmyra palm fruit shell activated carbon to adsorb Mn and Fe metals in manganese washing waste with adsorption efficiencies of 66.46% and 77.51% respectively. The low adsorption efficiency obtained is associated with many of the carbonized residues that are non-porous (Kayadoe et al, 2020).…”
Section: Methyl Red Adsorption Using Palmyra Palm Fruit Shell Activat...mentioning
confidence: 99%
“…Goa, et al (2014) reported the use of palmyra palm fruit shell activated carbon to adsorb Mn and Fe metals in manganese washing waste with adsorption efficiencies of 66.46% and 77.51% respectively. The low adsorption efficiency obtained is associated with many of the carbonized residues that are non-porous (Kayadoe et al, 2020).…”
Section: Methyl Red Adsorption Using Palmyra Palm Fruit Shell Activat...mentioning
confidence: 99%